44‐1: Invited Paper: Photolithography as Enabler of AMOLED Displays Beyond 1000 ppi. Issue 1 (May 2017) - Malinowski, Paweł E.; Ke, TungHuei; Nakamura, Atsushi; Vicca, Peter; Kronemeijer, Auke Jisk; Ameys, Marc; van der Steen, Jan Laurens; Steudel, Sören; Kamochi, Yoshitaka; Iwai, Yu; Gelinck, Gerwin; Heremans, Paul
Abstract : This paper describes the potential of hi‐res display fabrication using OLED photolithography. We demonstrate 1250 ppi multicolor arrays, pixel scaling down to 3 μm pitch, integration in active displays, and improving lifetime after patterning (200 hours T75, smOLEDs). Photolithography can enable low‐cost, high resolution displays for the 8K – VR era.